Consumption of fresh fruit rich in vitamin C and wheezing symptoms in children. Issue 4 (1st April 2000) - Forastiere, Francesco; Pistelli, Riccardo; Sestini, Piersante; Fortes, Cristina; Renzoni, Elisabetta; Rusconi, Franca; Dell'Orco, Valerio; Ciccone, Giovannino; Bisanti, Luigi; ,
Abstract : BACKGROUND: A beneficial effect of fresh fruit consumption on lung function has been observed in several studies. The epidemiological evidence of the effect on respiratory symptoms and asthma is limited. The consumption of fruit rich in vitamin C was examined in relation to wheezing and other respiratory symptoms in cross sectional and follow up studies of Italian children. METHODS: Standardised respiratory questionnaires were filled in by parents of 18 737 children aged 6–7 years living in eight areas of Northern and Central Italy. The winter intake of citrus fruit and kiwi fruit by the children was categorised as less than once per week, 1–2 per week, 3–4 per week, and 5–7 per week. A subset of 4104 children from two areas was reinvestigated after one year using a second parental questionnaire to record the occurrence of wheezing symptoms over the intervening period. RESULTS: In the cross sectional analysis, after controlling for several confounders (sex, study area, paternal education, household density, maternal smoking, paternal smoking, dampness or mould in the child's bedroom, parental asthma), intake of citrus fruit or kiwi fruit was a highly significant protective factor for wheeze in the last 12 months (odds ratio (OR) = 0.66, 95% confidence intervals (CI) 0.55 to 0.78, for those eating fruit 5–7 times per week compared with less than once per week), shortness of breath with wheeze (OR = 0.68, 95% CI 0.56 to 0.84), severe wheeze (OR = 0.59, 95% CI 0.40 to 0.85), nocturnal cough (OR = 0.73, 95% CI 0.65 to 0.83), chronic cough (OR = 0.75, 95% CI 0.65 to 0.88), and non-coryzal rhinitis (OR = 0.72, 95% CI 0.63 to 0.83). In the follow up study fruit intake recorded at baseline was a strong and independent predictor of all symptoms investigated except non-coryzal rhinitis. In most cases the protective effect was evident even among children whose intake of fruit was only 1–2 times per week and no clear dose-response relationship was found. The effect was stronger (although not significantly so (p = 0.13)) in subjects with a history of asthma; those eating fresh fruit at least once a week experienced a lower one year occurrence of wheeze (29.3%) than those eating fruit less than once per week (47.1%) (OR = 0.46, 95% CI 0.27 to 0.81). CONCLUSIONS: Although the effect of other dietary components cannot be excluded, it is concluded that the consumption of fruit rich in vitamin C, even at a low level of intake, may reduce wheezing symptoms in childhood, especially among already susceptible individuals.